Gender as a Differentiating Factor in Mathematics Anxiety of Pre-Service Teachers - Erika Franco-Buriticá; Iris Betzaida Pérez Almeida; Carmen León-Mantero; José Carlos Casas-Rosal (MDPI AG, 2023)
Developing mathematical competencies in future teachers requires particular attention to both cognitive and affective aspects. A positive attitude towards mathematics increases enjoyment, motivation, and confidence when working with the subject. It also reduces the anxiety of facing activities and problems and gives greater value to the academic and professional usefulness of mastering mathematical knowledge. These attitudes will also be reflected in their future teaching practice. For this reason, it is of great interest to study the attitudes of this critical group since, despite the numerous investigations carried out in this field, the influence of variables, such as place of origin or gender, on the attitudes and, in particular, on the attitudinal factor that best explains them, anxiety towards mathematics, has not yet been clarified. This work has analyzed the attitude and anxiety of 235 future teachers who study in rural and urban environments. The results show that gender is a differentiating factor in anxiety, with similar results in the schools of the two environments. However, the differences between men and women are more pronounced in the rural environment.